SUCCESSFUL GENETIC CHARACTERIZATION OF BULLET TUNA (Auxis rochei) USING MICROSATELLITE MARKERS IN KARANGASEM BALI - Maya Agustina; Made Pharmawati; Ketut Junitha (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2021)
Bullet Tuna (Auxis rochei) is classified under the neritic tuna group, which plays an essential role in small-scale fisheries in Karangasem Bali. The increasing catch of bullet tuna indicated its stock probably under threat. Therefore, genetic characterization is often required as the first step before building a conservation program. This study aims to categorize bullet tuna DNA using microsatellite. Of all five loci used, all were high polymorphism-type, with the number of alleles per locus varied between 18-27. Successful PCR (Polymerase Chain Reaction) created relatively high DNA concentration, ranging from 27.050 to 237.05 ng/ul, with a DNA purity level ranging from 2.073 to 2.239. Overall, the stock condition allegedly still in good condition, marked with high genes diversity (Ho=0.367-0.767 and He=0.934-0.966). All loci used can be amplified and well described.